PARAMETRIC OPTIMIZATION OF FERULIC ACID ESTERASE PRODUCTION FROM MUCOR HIEMALIS NCIM 837PARAMETRIC OPTIMIZATION OF FERULIC ACID ESTERASE PRODUCTION FROM MUCOR HIEMALIS NCIM 837 - Singh, Surabhi; Nigam, Vinod Kumar; Sachan, Ashish (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To optimize the parametric conditions for the production of ferulic acid esterase from Mucor hiemalis NCIM837 using HPLC for quantification. Methods: The experiments were conducted to determine the influence of pH and temperature on ferulic acid esterase production. To optimize the suitable agricultural waste, carbon source and the nitrogen source, different agricultural wastes, nitrogen sources and carbon sources were examined. Released ferulic acid was confirmed using HPLC. Results: Among the different agricultural waste residues screened, maize bran was identified as most suitable for ferulic acid esterase production with activity 143U/mg. Soyabean meal as the nitrogen source and sucrose as the additional carbon source was observed as the most effective in Ferulic acid ester production. Overall enzyme production increased by 2.2-fold as compared with un-optimized conditions. One unit of FAE was defined as the amount of enzyme required for release of 1Âµmole of FA per minute. Conclusion: Mucor hiemalis, to the best of our knowledge, is the new addition in the list of FAE producing microorganisms. No detailed studies on FAE production using Mucor hiemalis have been published so far. Â 